An Analysis of the Impact of Education and Experience on Ethical Reasoning in the Accounting Profession - Epperson, Kristen (Missouri Southern State University (Joplin, Mo.), 2012)
Abstract: A study to determine the differences in ethical reasoning between accounting students and professionals, and evaluate the effect education, experience and age may have on those decisions. Ethical theories used to measure and analyze the surveys include justice, deontology, relativism, utilitarianism, and neuroethics.; 18 pages : PDF file ; cm.